2021
DOI: 10.1177/2167479520961370
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Body of Turkish Bikini Fitness Athletes on Instagram

Abstract: This study sought to understand how Turkish bikini fitness athletes discipline their bodies on Instagram by using Foucault’s theorization of self-surveillance. We examined Instagram photos of 10 bikini fitness athletes and completed interviews with them. We analysed data by conducting quantitative and qualitative content analysis. The findings show that both bikini fitness and Instagram are modern forms of self-surveillance for Turkish female athletes. Bikini fitness dictates (hetero)normative femininity norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
5
0
5
Order By: Relevance
“…In non-Western digital cultures, resistance is explored not only in relation to patriarchal and masculinist norms, but to the religious and cultural norms that enact appropriate feminine embodiment and styles of presentation. For example, Kavasoğlu and Koca (2022) note that for Turkish women, criticisms around muscularity are shaped not only by sexism but by religio-conservative ideals that frame the display of the body as a transgression of social and religious expectations for women to remain concealed and docile.…”
Section: Digital Practices and Networked Bodiesmentioning
confidence: 99%
“…In non-Western digital cultures, resistance is explored not only in relation to patriarchal and masculinist norms, but to the religious and cultural norms that enact appropriate feminine embodiment and styles of presentation. For example, Kavasoğlu and Koca (2022) note that for Turkish women, criticisms around muscularity are shaped not only by sexism but by religio-conservative ideals that frame the display of the body as a transgression of social and religious expectations for women to remain concealed and docile.…”
Section: Digital Practices and Networked Bodiesmentioning
confidence: 99%
“…Since gender-based power relations are complex, it is important to understand the experiences of cyber violence specific to the gender regime of sportswomen and ways to combat it. For example, while Western sportswomen are exposed to forms of cyber violence such as racism, sexism, homophobia, misogyny, sexual harassment, physical threats, and sexual propositions (Kavanagh et al, 2019;Litchfield et al, 2018;Osborne et al, 2021), sportswomen in Muslim countries may struggle more often with religious patriarchal norms (Kavasoglu & Koca, 2022). Rahikainen and Toffoletti (2021) applied the theoretical framework of the "athletic labor of femininity" to explore sportswomen's decision-making processes in producing social media content by interviewing 27 sponsored female climbers and 5 industry professionals.…”
Section: Female Athletes Social Media and Cyber Violencementioning
confidence: 99%
“…These studies revealed the opportunities and risks that social media presents for female athletes. However, in Turkey, research addressing representations of women via social media is both limited and new (Kavasoğlu & Koca, 2022). We need further studies to understand the opportunities and challenges of using social media for female athletes from Turkey and room for their voices must also be made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Örneğin erkek kimliğinin inşasında önemli görülen vücut geliştirme alanında kadın sporcular, cinsiyet kimlikleri ve cinsel yönelimlerinin sorgulanmaması için cisheteroseksüel kadınlıklarını vurgulamak durumunda kalmaktadırlar (Kavasoğlu ve Macit, 2018;Kavasoğlu ve Koca, 2019). Dahası vücut geliştirme ve fitness alanının bikini fitness kategorisinde kadın sporcular kaslı fakat seksi olduklarını göstermek için tepeden tırnağa tüm bedenlerine ve beden hareketlerine, bakışlarına, jest ve mimiklerine dikkat etmektedirler (Kavasoğlu ve Koca, 2021).…”
Section: Kadın Sporcuların Bedenlerini Foucault'nun Kavramsal Araçlar...unclassified